Electrical Resistivity Imaging on Limestone Formation for Aquifers Identification in Poguwatu Village, Central Sumba - Nareswari, Aulia; Paembonan, Andri Yadi; Ruchimat, Acep (Jurnal Phi: Kurnal Pendidikan Fisika & Terapan, 2026)
Poguwatu Village in Central Sumba Regency is a dry area characterized by low rainfall and dominated by carbonate rocks, resulting in limited surface water availability and posing a persistent challenge for groundwater exploration. This study presents the first subsurface investigation using the Dipole-dipole resistivity geoelectrical method to characterize aquifer-bearing rock conducted in Poguwatu Village, West Cendana. This method has the ability to identify the conductor zone related to the saturation area where the water accumulated. Measurements were conducted along 5 survey lines, where each line has 620 m length, except Line 5 extending to 880 m, with 10 m electrode spacing. The measured data calculate in apparent resistivity value and then invert to true resistivity using least-square inversion processes. The result yielded RMS errors ranging from 17.7% to 24.8%. The inversion results identified four rock units based on resistivity values, sandy limestone saturated with saline water (< 2.0 Ωm), marl (2.0–32.0 Ωm), fractured or sandy limestone (32.0–128.0 Ωm), and compact limestone (>128.0 Ωm). A seepage with thickness ± 2 m was identified on Line 2 within the fractured/sandy limestone, bounded below by an impermeable marl. Compact limestone, with very low porosity and permeability, dominates in most of the study area and functions as an aquifuge, a finding corroborated by a dry borehole on Line 5 that failed to yield groundwater. These results indicate limited groundwater potential across Poguwatu Village, and further investigation into alternative water sources from surrounding areas is recommended for the community's water supply.